(untitled) (Tạp chí Y học Cộng đồng, 2023)
Background: Blood and blood products are a unique and precious national resource for its sole source from voluntary donation. Knowledge of blood donation has a great influence on people’s motivation. As the pioneering force in enhancing the healthcare practice, students of medicine should be able to improve the knowledge of blood donation for donors and encourage them to participate in this beneficial activity. Objective: This study aimed at surveying the knowledge of blood donation of medical students in Ho Chi Minh City in 2023. Method: A cross-sectional study on 780 health students was conducted in February 2023. Results: The blood donation knowledge questionnaire recorded 75% of the questions, with a correct answer rate of over 60%. Most of surveyed medical students have knowledge of required blood tests for donation (n=764; 97.9%) and the maximum age of blood donors (n=711; 91.2%). The Chisquare/Fisher test shows that there is a relationship between gender (p = 0.057), levels (p = 0.007), and religions (p = 0.035) and students’ knowledge of blood donation. Conclusion: Student health has adequate knowledge of blood donation, but there is still knowledge gap that can negatively affect students’ motivation to practice blood donation.